2023
DOI: 10.14744/tjtes.2023.78166
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy guided without contrast injection for ganglion impar blockade in traumatic coccydynia: Description a modified approach and one-year results

Abstract: tailbone. The most common cause of coccydynia is trauma, especially recurrent microtraumas and falls, resulting in difficulty in sitting and short sitting times, with the contribution of the postpartum hypermobile coccyx, or chronic inflammatory diseases. [3] It has been reported that some anatomical and morphological changes may cause pain when people with coccydynia are compared to the normal population. [4] According to Postacchini, the coccyx is classified in four types. [5] However, the literature studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…In the same studies, they found the intercoccygeal angle to be 132.2 and 131 degrees, respectively. Again, in the same studies, they found the coccygeal length to be 26 and 34.7 mm, respectively [5,23] . In our study, we found the mean sacrococcygeal and intercoccygeal angles to be 116.8 and 138 degrees, respectively.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the same studies, they found the intercoccygeal angle to be 132.2 and 131 degrees, respectively. Again, in the same studies, they found the coccygeal length to be 26 and 34.7 mm, respectively [5,23] . In our study, we found the mean sacrococcygeal and intercoccygeal angles to be 116.8 and 138 degrees, respectively.…”
Section: Discussionmentioning
confidence: 72%
“…It has been shown in the literature that coccydynia is associated with some radiological parameters. In the classification made by Postacchini et al, the most common type of coccyx was found to be type 1, while Yoon et al and Kaya et al found type 2 coccyx [5,23,24] . In our study, we found 23.1% type1, 46.2% type2, 23.1% type 3 and 7.7% type 4 coccyx.…”
Section: Discussionmentioning
confidence: 98%